A group is called ``abelian`` if its operation is commutative, i.e. \(P\langle a,b \rangle = P\langle a,b \rangle\) for all group elements \(a,b\), where \(P\) is the group operation. It is customary to use the additive notation for abelian groups, so this condition is typically written as \(a+b = b+a\). We will be using multiplicative notation though (in which the commutativity condition of the operation is written as \(a\cdot b = b\cdot a\)), just to avoid the hassle of changing the notation we used for general groups.
This section is not interesting and should not be read. Here we will prove formulas is which right hand side uses the same factors as the left hand side, just in different order. These facts are obvious in informal math sense, but Isabelle prover is not able to derive them automatically, so we have to prove them by hand.
Proving the facts about associative and commutative operations is quite tedious in formalized mathematics. To a human the thing is simple: we can arrange the elements in any order and put parantheses wherever we want, it is all the same. However, formalizing this statement would be rather difficult (I think). The next lemma attempts a quasi-algorithmic approach to this type of problem. To prove that two expressions are equal, we first strip one from parantheses, then rearrange the elements in proper order, then put the parantheses where we want them to be. The algorithm for rearrangement is easy to describe: we keep putting the first element (from the right) that is in the wrong place at the left-most position until we get the proper arrangement. As far removing parantheses is concerned Isabelle does its job automatically.
lemma (in group0) group0_4_L2:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \), \( c\in G \), \( d\in G \), \( E\in G \), \( F\in G \)
shows \( (a\cdot b)\cdot (c\cdot d)\cdot (E\cdot F) = (a\cdot (d\cdot F))\cdot (b\cdot (c\cdot E)) \)proofAnother useful rearrangement.
lemma (in group0) group0_4_L3:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \) and A3: \( c\in G \), \( d\in G \), \( E\in G \), \( F\in G \)
shows \( a\cdot b\cdot ((c\cdot d)^{-1}\cdot (E\cdot F)^{-1}) = (a\cdot (E\cdot c)^{-1})\cdot (b\cdot (F\cdot d)^{-1}) \)proofSome useful rearrangements for two elements of a group.
lemma (in group0) group0_4_L4:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \)
shows \( b^{-1}\cdot a^{-1} = a^{-1}\cdot b^{-1} \), \( (a\cdot b)^{-1} = a^{-1}\cdot b^{-1} \), \( (a\cdot b^{-1})^{-1} = a^{-1}\cdot b \)proofAnother bunch of useful rearrangements with three elements.
lemma (in group0) group0_4_L4A:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \), \( c\in G \)
shows \( a\cdot b\cdot c = c\cdot a\cdot b \), \( a^{-1}\cdot (b^{-1}\cdot c^{-1})^{-1} = (a\cdot (b\cdot c)^{-1})^{-1} \), \( a\cdot (b\cdot c)^{-1} = a\cdot b^{-1}\cdot c^{-1} \), \( a\cdot (b\cdot c^{-1})^{-1} = a\cdot b^{-1}\cdot c \), \( a\cdot b^{-1}\cdot c^{-1} = a\cdot c^{-1}\cdot b^{-1} \)proofAnother useful rearrangement.
lemma (in group0) group0_4_L4B:
assumes \( P \text{ is commutative on } G \) and \( a\in G \), \( b\in G \), \( c\in G \)
shows \( a\cdot b^{-1}\cdot (b\cdot c^{-1}) = a\cdot c^{-1} \) using assms, inverse_in_group, group_op_closed, group0_4_L4, group_oper_assoc, inv_cancel_twoA couple of permutations of order for three alements.
lemma (in group0) group0_4_L4C:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \), \( c\in G \)
shows \( a\cdot b\cdot c = c\cdot a\cdot b \), \( a\cdot b\cdot c = a\cdot (c\cdot b) \), \( a\cdot b\cdot c = c\cdot (a\cdot b) \), \( a\cdot b\cdot c = c\cdot b\cdot a \)proofSome rearangement with three elements and inverse.
lemma (in group0) group0_4_L4D:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \), \( c\in G \)
shows \( a^{-1}\cdot b^{-1}\cdot c = c\cdot a^{-1}\cdot b^{-1} \), \( b^{-1}\cdot a^{-1}\cdot c = c\cdot a^{-1}\cdot b^{-1} \), \( (a^{-1}\cdot b\cdot c)^{-1} = a\cdot b^{-1}\cdot c^{-1} \)proofAnother rearrangement lemma with three elements and equation.
lemma (in group0) group0_4_L5:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \), \( c\in G \) and A3: \( c = a\cdot b^{-1} \)
shows \( a = b\cdot c \)proofIn abelian groups we can cancel an element with its inverse even if separated by another element.
lemma (in group0) group0_4_L6A:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \)
shows \( a\cdot b\cdot a^{-1} = b \), \( a^{-1}\cdot b\cdot a = b \), \( a^{-1}\cdot (b\cdot a) = b \), \( a\cdot (b\cdot a^{-1}) = b \)proofAnother lemma about cancelling with two elements.
lemma (in group0) group0_4_L6AA:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \)
shows \( a\cdot b^{-1}\cdot a^{-1} = b^{-1} \) using assms, inverse_in_group, group0_4_L6AAnother lemma about cancelling with two elements.
lemma (in group0) group0_4_L6AB:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \)
shows \( a\cdot (a\cdot b)^{-1} = b^{-1} \), \( a\cdot (b\cdot a^{-1}) = b \)proofAnother lemma about cancelling with two elements.
lemma (in group0) group0_4_L6AC:
assumes \( P \text{ is commutative on } G \) and \( a\in G \), \( b\in G \)
shows \( a\cdot (a\cdot b^{-1})^{-1} = b \) using assms, inverse_in_group, group0_4_L6AB, group_inv_of_invIn abelian groups we can cancel an element with its inverse even if separated by two other elements.
lemma (in group0) group0_4_L6B:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \), \( c\in G \)
shows \( a\cdot b\cdot c\cdot a^{-1} = b\cdot c \), \( a^{-1}\cdot b\cdot c\cdot a = b\cdot c \)proofIn abelian groups we can cancel an element with its inverse even if separated by three other elements.
lemma (in group0) group0_4_L6C:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \), \( c\in G \), \( d\in G \)
shows \( a\cdot b\cdot c\cdot d\cdot a^{-1} = b\cdot c\cdot d \)proofAnother couple of useful rearrangements of three elements and cancelling.
lemma (in group0) group0_4_L6D:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \), \( c\in G \)
shows \( a\cdot b^{-1}\cdot (a\cdot c^{-1})^{-1} = c\cdot b^{-1} \), \( (a\cdot c)^{-1}\cdot (b\cdot c) = a^{-1}\cdot b \), \( a\cdot (b\cdot (c\cdot a^{-1}\cdot b^{-1})) = c \), \( a\cdot b\cdot c^{-1}\cdot (c\cdot a^{-1}) = b \)proofAnother useful rearrangement of three elements and cancelling.
lemma (in group0) group0_4_L6E:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \), \( c\in G \)
shows \( a\cdot b\cdot (a\cdot c)^{-1} = b\cdot c^{-1} \)proofA rearrangement with two elements and canceelling, special case of group0_4_L6D when \(c=b^{-1}\).
lemma (in group0) group0_4_L6F:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \)
shows \( a\cdot b^{-1}\cdot (a\cdot b)^{-1} = b^{-1}\cdot b^{-1} \)proofSome other rearrangements with four elements. The algorithm for proof as in group0_4_L2 works very well here.
lemma (in group0) rearr_ab_gr_4_elemA:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \), \( c\in G \), \( d\in G \)
shows \( a\cdot b\cdot c\cdot d = a\cdot d\cdot b\cdot c \), \( a\cdot b\cdot c\cdot d = a\cdot c\cdot (b\cdot d) \)proofSome rearrangements with four elements and inverse that are applications of rearr_ab_gr_4_elem
lemma (in group0) rearr_ab_gr_4_elemB:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \), \( c\in G \), \( d\in G \)
shows \( a\cdot b^{-1}\cdot c^{-1}\cdot d^{-1} = a\cdot d^{-1}\cdot b^{-1}\cdot c^{-1} \), \( a\cdot b\cdot c\cdot d^{-1} = a\cdot d^{-1}\cdot b\cdot c \), \( a\cdot b\cdot c^{-1}\cdot d^{-1} = a\cdot c^{-1}\cdot (b\cdot d^{-1}) \)proofSome rearrangement lemmas with four elements.
lemma (in group0) group0_4_L7:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \), \( c\in G \), \( d\in G \)
shows \( a\cdot b\cdot c\cdot d^{-1} = a\cdot d^{-1}\cdot b\cdot c \), \( a\cdot d\cdot (b\cdot d\cdot (c\cdot d))^{-1} = a\cdot (b\cdot c)^{-1}\cdot d^{-1} \), \( a\cdot (b\cdot c)\cdot d = a\cdot b\cdot d\cdot c \)proofSome other rearrangements with four elements.
lemma (in group0) group0_4_L8:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \), \( c\in G \), \( d\in G \)
shows \( a\cdot (b\cdot c)^{-1} = (a\cdot d^{-1}\cdot c^{-1})\cdot (d\cdot b^{-1}) \), \( a\cdot b\cdot (c\cdot d) = c\cdot a\cdot (b\cdot d) \), \( a\cdot b\cdot (c\cdot d) = a\cdot c\cdot (b\cdot d) \), \( a\cdot (b\cdot c^{-1})\cdot d = a\cdot b\cdot d\cdot c^{-1} \), \( (a\cdot b)\cdot (c\cdot d)^{-1}\cdot (b\cdot d^{-1})^{-1} = a\cdot c^{-1} \)proofSome other rearrangements with four elements.
lemma (in group0) group0_4_L8A:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \), \( c\in G \), \( d\in G \)
shows \( a\cdot b^{-1}\cdot (c\cdot d^{-1}) = a\cdot c\cdot (b^{-1}\cdot d^{-1}) \), \( a\cdot b^{-1}\cdot (c\cdot d^{-1}) = a\cdot c\cdot b^{-1}\cdot d^{-1} \)proofSome rearrangements with an equation.
lemma (in group0) group0_4_L9:
assumes A1: \( P \text{ is commutative on } G \) and A2: \( a\in G \), \( b\in G \), \( c\in G \), \( d\in G \) and A3: \( a = b\cdot c^{-1}\cdot d^{-1} \)
shows \( d = b\cdot a^{-1}\cdot c^{-1} \), \( d = a^{-1}\cdot b\cdot c^{-1} \), \( b = a\cdot d\cdot c \)proofassumes \( a\in G \), \( b\in G \)
shows \( a\cdot b \in G \)assumes \( a\in G \), \( b\in G \), \( c\in G \)
shows \( a\cdot (b\cdot c) = a\cdot b\cdot c \)assumes \( x\in G \)
shows \( x^{-1}\in G \)assumes \( a\in G \) and \( b\in G \)
shows \( b^{-1}\cdot a^{-1} = (a\cdot b)^{-1} \)assumes \( P \text{ is commutative on } G \) and \( a\in G \), \( b\in G \), \( c\in G \), \( d\in G \), \( E\in G \), \( F\in G \)
shows \( (a\cdot b)\cdot (c\cdot d)\cdot (E\cdot F) = (a\cdot (d\cdot F))\cdot (b\cdot (c\cdot E)) \)assumes \( a\in G \)
shows \( a = (a^{-1})^{-1} \)assumes \( P \text{ is commutative on } G \) and \( a\in G \), \( b\in G \)
shows \( b^{-1}\cdot a^{-1} = a^{-1}\cdot b^{-1} \), \( (a\cdot b)^{-1} = a^{-1}\cdot b^{-1} \), \( (a\cdot b^{-1})^{-1} = a^{-1}\cdot b \)assumes \( a\in G \), \( b\in G \)
shows \( a\cdot b^{-1}\cdot b = a \), \( a\cdot b\cdot b^{-1} = a \), \( a^{-1}\cdot (a\cdot b) = b \), \( a\cdot (a^{-1}\cdot b) = b \)assumes \( P \text{ is commutative on } G \) and \( a\in G \), \( b\in G \), \( c\in G \)
shows \( a\cdot b\cdot c = c\cdot a\cdot b \), \( a^{-1}\cdot (b^{-1}\cdot c^{-1})^{-1} = (a\cdot (b\cdot c)^{-1})^{-1} \), \( a\cdot (b\cdot c)^{-1} = a\cdot b^{-1}\cdot c^{-1} \), \( a\cdot (b\cdot c^{-1})^{-1} = a\cdot b^{-1}\cdot c \), \( a\cdot b^{-1}\cdot c^{-1} = a\cdot c^{-1}\cdot b^{-1} \)assumes \( a\in G \), \( b\in G \), \( c\in G \)
shows \( (a\cdot b\cdot c)^{-1} = c^{-1}\cdot (a\cdot b)^{-1} \), \( (a\cdot b\cdot c)^{-1} = c^{-1}\cdot (b^{-1}\cdot a^{-1}) \), \( (a\cdot b\cdot c)^{-1} = c^{-1}\cdot b^{-1}\cdot a^{-1} \)assumes \( P \text{ is commutative on } G \) and \( a\in G \), \( b\in G \), \( c\in G \)
shows \( a\cdot b\cdot c = c\cdot a\cdot b \), \( a\cdot b\cdot c = a\cdot (c\cdot b) \), \( a\cdot b\cdot c = c\cdot (a\cdot b) \), \( a\cdot b\cdot c = c\cdot b\cdot a \)assumes \( a\in G \), \( b\in G \) and \( c = a\cdot b \)
shows \( c\cdot b^{-1} = a \), \( a^{-1}\cdot c = b \)assumes \( x\in G \)
shows \( x\cdot x^{-1} = 1 \wedge x^{-1}\cdot x = 1 \)assumes \( P \text{ is commutative on } G \) and \( a\in G \), \( b\in G \)
shows \( a\cdot b\cdot a^{-1} = b \), \( a^{-1}\cdot b\cdot a = b \), \( a^{-1}\cdot (b\cdot a) = b \), \( a\cdot (b\cdot a^{-1}) = b \)assumes \( P \text{ is commutative on } G \) and \( a\in G \), \( b\in G \)
shows \( a\cdot b^{-1}\cdot a^{-1} = b^{-1} \)assumes \( P \text{ is commutative on } G \) and \( a\in G \), \( b\in G \)
shows \( a\cdot (a\cdot b)^{-1} = b^{-1} \), \( a\cdot (b\cdot a^{-1}) = b \)assumes \( a\in G \), \( b\in G \)
shows \( (a\cdot b^{-1})^{-1} = b\cdot a^{-1} \), \( (a^{-1}\cdot b)^{-1} = b^{-1}\cdot a \)assumes \( P \text{ is commutative on } G \) and \( a\in G \), \( b\in G \), \( c\in G \)
shows \( a\cdot b\cdot c\cdot a^{-1} = b\cdot c \), \( a^{-1}\cdot b\cdot c\cdot a = b\cdot c \)assumes \( P \text{ is commutative on } G \) and \( a\in G \), \( b\in G \), \( c\in G \)
shows \( a\cdot b^{-1}\cdot (a\cdot c^{-1})^{-1} = c\cdot b^{-1} \), \( (a\cdot c)^{-1}\cdot (b\cdot c) = a^{-1}\cdot b \), \( a\cdot (b\cdot (c\cdot a^{-1}\cdot b^{-1})) = c \), \( a\cdot b\cdot c^{-1}\cdot (c\cdot a^{-1}) = b \)assumes \( P \text{ is commutative on } G \) and \( a\in G \), \( b\in G \), \( c\in G \), \( d\in G \)
shows \( a\cdot b\cdot c\cdot d = a\cdot d\cdot b\cdot c \), \( a\cdot b\cdot c\cdot d = a\cdot c\cdot (b\cdot d) \)assumes \( a\in G \), \( b\in G \), \( c\in G \)
shows \( a\cdot c^{-1}= (a\cdot b^{-1})\cdot (b\cdot c^{-1}) \), \( a^{-1}\cdot c = (a^{-1}\cdot b)\cdot (b^{-1}\cdot c) \), \( a\cdot (b\cdot c)^{-1} = a\cdot c^{-1}\cdot b^{-1} \), \( a\cdot (b\cdot c^{-1}) = a\cdot b\cdot c^{-1} \), \( (a\cdot b^{-1}\cdot c^{-1})^{-1} = c\cdot b\cdot a^{-1} \), \( a\cdot b\cdot c^{-1}\cdot (c\cdot b^{-1}) = a \), \( a\cdot (b\cdot c)\cdot c^{-1} = a\cdot b \)assumes \( P \text{ is commutative on } G \) and \( a\in G \), \( b\in G \), \( c\in G \), \( d\in G \)
shows \( a\cdot b\cdot c\cdot d^{-1} = a\cdot d^{-1}\cdot b\cdot c \), \( a\cdot d\cdot (b\cdot d\cdot (c\cdot d))^{-1} = a\cdot (b\cdot c)^{-1}\cdot d^{-1} \), \( a\cdot (b\cdot c)\cdot d = a\cdot b\cdot d\cdot c \)assumes \( P \text{ is commutative on } G \) and \( a\in G \), \( b\in G \), \( c\in G \), \( d\in G \)
shows \( a\cdot (b\cdot c)^{-1} = (a\cdot d^{-1}\cdot c^{-1})\cdot (d\cdot b^{-1}) \), \( a\cdot b\cdot (c\cdot d) = c\cdot a\cdot (b\cdot d) \), \( a\cdot b\cdot (c\cdot d) = a\cdot c\cdot (b\cdot d) \), \( a\cdot (b\cdot c^{-1})\cdot d = a\cdot b\cdot d\cdot c^{-1} \), \( (a\cdot b)\cdot (c\cdot d)^{-1}\cdot (b\cdot d^{-1})^{-1} = a\cdot c^{-1} \)